Nghiên cứu bệnh phẩm cây sup lơ xanh (Brassica oleracea L. Vả. botrytis L.) - Hoàng, Thị Sâm (Trường Đại học Đà Lạt, 2012)
Aresearch on diseased samples of broccoli plants. Broccoli (Brassica olearcea L. Var. botrytis L.), valuable vegetable species of the family Brassicaceae or Cruciferae is widely grown at Dalat, Lam Dong. The club root desease os this cultivar has reduced its yield and quality.